On the reticular construction concept of covalent organic frameworks - Lukose, Binit; Kuc, Agnieszka; Frenzel, Johannes; Heine, Thomas (Beilstein Journal of Nanotechnology, 2010)
The concept of reticular chemistry is investigated to explore the applicability of the formation of Covalent Organic Frameworks (COFs) from their defined individual building blocks. Thus, we have designed, optimized and investigated a set of reported and hypothetical 2D COFs using Density Functional Theory (DFT) and the related Density Functional based tight-binding (DFTB) method. Linear, trigonal and hexagonal building blocks have been selected for designing hexagonal COF layers. High-symmetry AA and AB stackings are considered, as well as low-symmetry serrated and inclined stackings of the layers. The latter ones are only slightly modified compared to the high-symmetry forms, but show higher energetic stability. Experimental XRD patterns found in literature also support stackings with highest formation energies. All stacking forms vary in their interlayer separations and band gaps; however, their electronic densities of states (DOS) are similar and not significantly different from that of a monolayer. The band gaps are found to be in the range of 1.7–4.0 eV. COFs built of building blocks with a greater number of aromatic rings have smaller band gaps.
Keywords: covalent organic frameworks; DFTB; energetic and electronic properties; layer stacking; XRD